2009
DOI: 10.1097/qai.0b013e31819c2937
|View full text |Cite
|
Sign up to set email alerts
|

A Once-Daily Lopinavir/Ritonavir-Based Regimen Is Noninferior to Twice-Daily Dosing and Results in Similar Safety and Tolerability in Antiretroviral-Naive Subjects Through 48 Weeks

Abstract: At 48 weeks, the antiviral response in the LPV/r once-daily group was noninferior to the twice-daily group when coadministered with tenofovir and emtricitabine in antiretroviral-naive subjects. Efficacy was comparable between the once-daily and twice-daily groups regardless of baseline HIV-1 RNA or CD4+ T-cell count. Safety and tolerability of once-daily and twice-daily dosing was also comparable. No new PI resistance mutations were detected upon virologic rebound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 17 publications
0
35
1
Order By: Relevance
“…LPV/r has also been studied and is registered in the USA at the dose 800/ 200 q.d in treatment-naïve patients. Although this dose has been demonstrated to be "non-inferior" to 400/100 b.i.d [32,33], it is still to some extent a matter of contention whether it is equally efficacious [34]. A published PK/PD analysis on the relation between LPV concentration and effect in patients receiving these doses, as well as 800/200 q.d., states that no relation between drug concentration and antiretroviral effect was observed within the range of LPV exposures investigated [35].…”
Section: Discussionmentioning
confidence: 99%
“…LPV/r has also been studied and is registered in the USA at the dose 800/ 200 q.d in treatment-naïve patients. Although this dose has been demonstrated to be "non-inferior" to 400/100 b.i.d [32,33], it is still to some extent a matter of contention whether it is equally efficacious [34]. A published PK/PD analysis on the relation between LPV concentration and effect in patients receiving these doses, as well as 800/200 q.d., states that no relation between drug concentration and antiretroviral effect was observed within the range of LPV exposures investigated [35].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertriglyceridemia and hypercholesterolemia have been reported in patients treated with the conventional dose of LPV/r. 21,27 However, during pregnancy, there is an increase of TG in the first trimester. 28 Lipids are used as an energy source for the fetus, and as precursors for bile acids and steroid hormones.…”
Section: Changes In Laboratory Testsmentioning
confidence: 99%
“…When using the conventional dose of LPV/r in men and non-pregnant women, diarrhea occurs in 39-57% of patients and nausea occurs in 11-15% of patients during the 1st year. 21,22 Among patients who were exposed to HIV while receiving a prophylactic ART regimen with LPV/r at the conventional doses of tenofovir and emtricitabine, there was a 78% incidence of diarrhea and 59% incidence of nausea during the first 28 days of use. 23 The lower rates of occurrence of diarrhea during pregnancy may be attributed to the constipation that occurs during pregnancy because of the progestational effect.…”
Section: Gi Eventsmentioning
confidence: 99%
“…However, the lopinavir AUC 0-12 and C 12 for patients taking 3 tablets BD plus NNRTIs are similar to those for patients taking 2 tablets BD without NNRTIs in whom lopinavir and ritonavir exposures were similar to that observed for studies in resource-rich settings (4). Low plasma C 12 values for patients taking 2 tablets BD plus NNRTIs may increase the risk of virological failure, although these levels are similar to the C trough values seen for patients taking 800/200 mg (4 tablets) four times a day (QD), which has shown good efficacy in patients without lopinavir resistance (6). Nevertheless, the fact that levels were lower than both those for patients taking 4 capsules BD with NNRTIs and those for patients taking 2 tablets BD without NNRTIs supports the most recent licensing information that a dose increment above 2 lopinavir-ritonavir tablets BD with concurrent NNRTIs should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Only the C max for the group receiving 2 lopinavir-ritonavir tablets BD with efavirenz was formally bioequivalent to 4 lopinavir-ritonavir capsules BD. Comparison of data for the group receiving 3 lopinavir-ritonavir tablets BD with NNRTI to data for the group receiving 2 lopinavirritonavir tablets BD without NNRTIs showed that the levels were generally similar those for the group receiving 3 tablets (50) 9 (45) 11 (55) 5 (28) 6 (33) 7 (39) 7 (35) 4 5 (25) 2 (10) 5 (25) 8 (44) 3 (17) 7 (39) 10 (50) 6 5 (25) 4 (20) 4 (20) 2 (11) 3 (17) 3 (17) 3 (15) 8 1 (5) 1 (6) Geometric mean C 12 (g/ml) (%CV) ͓range͔ 2.9 (189) ͓0.1-13.8͔ No. of patients (%) with C 12 (g/ml) of: Ͻ1 3 (15) 3 (15) 8 (40) 4 (22) 5 (28) 1-Ͻ5…”
Section: Resultsmentioning
confidence: 99%